2018
DOI: 10.1111/echo.14233
|View full text |Cite
|
Sign up to set email alerts
|

Fungal prosthetic aortic valve endocarditis and endarteritis: An unusual cause of aortic root vegetations

Abstract: Fungal endocarditis is a relatively rare occurrence with high morbidity and mortality. Patients may have an indolent and non‐specific course requiring a high index of suspicion to make a diagnosis. Here, we present the case of a 33‐year‐old patient who presented with fevers and acute lower limb ischemia requiring a 4‐compartment fasciotomy caused by septic emboli from Candida albicans endocarditis. The patient had a large vegetation in the ascending aorta associated with a mycotic aneurysm, which is an exceedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…In 86 reports, 91 cases of definitive fungal IE were described. These reports involved fifteen cases with Candida parapsilosis [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] , seven cases with C. albicans [55][56][57][58][59][60][61] , three cases with C. tropicalis [62][63][64] , eight other species with Candida [65][66][67][68][69][70][71][72] , eight cases with Candida with a bacterium [73][74][75][76][77][78][79][80] , ten cases with Aspergillus fumigatus [81][82][83][84][85][86][87][88][89]…”
Section: Case Reportsmentioning
confidence: 99%
See 3 more Smart Citations
“…In 86 reports, 91 cases of definitive fungal IE were described. These reports involved fifteen cases with Candida parapsilosis [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] , seven cases with C. albicans [55][56][57][58][59][60][61] , three cases with C. tropicalis [62][63][64] , eight other species with Candida [65][66][67][68][69][70][71][72] , eight cases with Candida with a bacterium [73][74][75][76][77][78][79][80] , ten cases with Aspergillus fumigatus [81][82][83][84][85][86][87][88][89]…”
Section: Case Reportsmentioning
confidence: 99%
“…In many cases with negative cultures or difficulties in identifying the infecting fungal microorganism, beta-D-glucan testing was performed. This was needed in a minority of Candida infections [51,54,55] but more often in Aspergillus [81,84,87,90,92,96] and certain other fungal species [101,106,107,118,[120][121][122][123][124] . Detection for the presence of galactomannan was also performed in IE by Aspergillus [85,89,92,93] and other uncommon species [112][113][114]120,121,125] .…”
Section: Case Reportsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently read with great interest the article by Carneiro et al entitled "Fungal prosthetic aortic valve endocarditis and endarteritis: An unusual cause of aortic root vegetations". 1 The authors reported a case of fungal aortic prosthetic valve endocarditis (PVE), which was successfully treated with antibiotic therapy plus surgical intervention. We congratulate the authors for achieving a successful outcome in such a high-risk patient.…”
Section: Fundamental Role Of Echocardiographic Evaluation In the Diagmentioning
confidence: 99%